1998
DOI: 10.1007/bf02383746
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion dialysis aided electrodialysis process for concentration of radionuclides in acid medium

Abstract: A study on the separation of the long-lived heat generating fission products 137Cs and 9~ from acidic solutions has been camed out using a specially fabricated electrodialytic cell equipped with a pair of cation and anion exchange membranes forming a catholyte and anolyte, respectively, and a radioactive feed chamber. The studies were done with feed solutions containing different concentrations of Na +, Cs + and Sr 2+ individually and with a mixture of these cations in 0.3M HNO 3. In all the cases, the transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…A comprehensive review of the technique was made by Smith et al (1999). Due to the nature of the Los Alamos National Laboratory (LANL)'s mission and their involvement in actinide separations work for many years, their first application of (Mathur et al 1998) this technology has been in the area of ultralow-level analysis of actinides and removal of actinides from process and waste streams. Bench-scale studies for actinide elimination from plutonium facility distillate waters were studied.…”
Section: Sieve Separation Mechanism Ultrafiltrationmentioning
confidence: 99%
“…A comprehensive review of the technique was made by Smith et al (1999). Due to the nature of the Los Alamos National Laboratory (LANL)'s mission and their involvement in actinide separations work for many years, their first application of (Mathur et al 1998) this technology has been in the area of ultralow-level analysis of actinides and removal of actinides from process and waste streams. Bench-scale studies for actinide elimination from plutonium facility distillate waters were studied.…”
Section: Sieve Separation Mechanism Ultrafiltrationmentioning
confidence: 99%
“…12 Areas such as chemical analysis for pre-concentration, extraction processes, hydrometallurgy, separating acids from their salts, radioactive flow deacidification, removal of copper and zinc using commercial cationic membranes, and removal of inorganic anions such as fluoride, nitrate, bromate, and borate from drinking water can all be achieved with Donnan dialysis. [13][14][15][16][17] The development of new materials with definitive properties can include interpenetrating polymer networks (IPNs), which is an alternative method to modify microporous membranes. When two or more polymer networks are partially and non-covalently crosslinked on the molecular scale, it allows the formation of IPN architectures.…”
Section: -mentioning
confidence: 99%
“…The results of these studies confirmed the high retention of carbonate ions and selective separation of molybdenum from uranium. Electrodialysis combined with diffusion dialysis was tested for the separation of 137 Cs and 90 Sr from concentrated nitric acid solutions [ 16 ]. Diffusion dialysis was conducted in a two-chamber system wherein the anion-exchange membrane and the reduction in solution acidity were involved in the first step of the proposed radioactive waste treatment scheme.…”
Section: Introductionmentioning
confidence: 99%